Recombinant expression of functional mouse AhR LBD in E. coli - Elhawari, Wail (2012)
2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) is a toxic halogenated aromatic hydrocarbon, which is a potent toxin to different species such as fish, birds, and mammalians. TCDD exposure causes induction of cytochrome P4501A1 (CYP1A1), and that is controlled through the Aryl hydrocarbon receptor (AhR). AhR is a ligand-dependent cytosolic protein. It is a protein containing basic helix-loop-helix and Per-ARNT-Sim (PAS) domains. It is present in the cytosol as a complex containing two molecules of heat shock protein (hsp90) and AhR interacting protein (AIP). When TCDD binds to AhR, the ligand–AHR complex translocates to the nucleus and dissociates from chaperone proteins and binds to another protein called ARNT (AhR nuclear translocator). The AhR-ARNT heterodimer then activates transcription. The three-dimensional structure of AhR is unknown, as is its interaction with ligands. The aim of this work is trying to produce a high level expression and purification of an AhR-GFP (AhR–green florescent protein) fusion protein functional and sufficient for fluorescence analytical techniques to study the ligand binding and the change in AhR conformation. Escherichia coli strain BL21 was used to express the recombinant protein since it is easy, cheap and yields a high level of protein. However, the attempts were not successful to express GST-EGFP-AhR (GGA) and GST-EGFP-AhR-EGFP (GGAG) recombinants in a functional conformation. By lowering the cultivation temperature, the proteins could be expressed and fold correctly in E. coli. However, E. coli does not contain the chaperon proteins essential for ligand binding. Therefore, the bacterially expressed protein was refolded in human reticulocyte lysate. This study established that GFP AhR (LBD) recombinant protein can be obtained in the ligand binding conformation through the expression of the protein in E coli followed by refolding in reticulocyte lysate.